2015
DOI: 10.1128/genomea.00314-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Ureaplasma diversum Strain ATCC 49782

Abstract: Here, we report the complete genome sequence of Ureaplasma diversum strain ATCC 49782. This species is of bovine origin, having an association with reproductive disorders in cattle, including placentitis, fetal alveolitis, abortion, and birth of weak calves. It has a small circular chromosome of 975,425 bp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…NF-κB and AP-1 regulate important genes associated with inflammation in infection processes ( Garcia et al, 1998 ; Rawadi et al, 1999 ). Accordingly, the recent genome analyses of U. diversum revealed a large number of genes encoding membrane-associated lipoproteins, as well as urease, hemolysin, phospholipase and glycosyltransferase (associated with capsule synthesis) enzymes ( Marques et al, 2015 , 2016 ). These lipoproteins, however, have never been separately analyzed for their host immune system stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB and AP-1 regulate important genes associated with inflammation in infection processes ( Garcia et al, 1998 ; Rawadi et al, 1999 ). Accordingly, the recent genome analyses of U. diversum revealed a large number of genes encoding membrane-associated lipoproteins, as well as urease, hemolysin, phospholipase and glycosyltransferase (associated with capsule synthesis) enzymes ( Marques et al, 2015 , 2016 ). These lipoproteins, however, have never been separately analyzed for their host immune system stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic cows may chronically carry U. diversum and function as pathogen reservoirs and are, therefore, a major source of infection. Bovine ureaplasmas have surface compounds, such as variable surface lipoproteins (VSPs) that allow them to evade the host's immune system, invade cells, and help develop chronic infection ( 28 , 42 , 88 90 ).…”
Section: Ureaplasma Diversummentioning
confidence: 99%
“…There is no data in the literature on the pathogenic effects of the expression of the urease gene by U. diversum ; however, in these bacteria, the urease genomic cluster was identified, with more than 90% homology to the human Ureaplasma spp. coding sequence (CDS) ( 28 , 90 ). Hydrolysis of urea in ureaplasma generates an electrochemical gradient through accumulation of intracellular ammonia/ammonium.…”
Section: Virulence Of U Diversummentioning
confidence: 99%
See 1 more Smart Citation
“…These antigens are considered the main molecular agents associated with pathogens in several Mollicutes species and play an important role in host pathogenicity and immunomodulation [7]. In addition to lipoproteins, in the bovine ureaplasma genome, our research group identified genes encoding the multiple band antigen (MBA), which contain multiple series repetitions in the C-terminal region, as well as the gene for hemolysin and for the Mycoplasma Ig binding protein (MIB) and Mycoplasma Ig protease (MIP) -MIB-MIP system-, which acts by binding and cleaving the IgG heavy chain [2,8].…”
Section: Introductionmentioning
confidence: 99%